Late Diagnosis in oral squamous cell carcinoma, the role of psychological and cognitive variables - Mehmood Ahmed Rana, Mahesh Kumar Luhano, Ihsanullah Khan, Maria Noor, Nighat Zahid, Anam Akram (Pakistan Journal of Medical & Health Sciences, 2022)
This retrospective study investigated, in two cohorts of subjects living in Karachi Pakistan and awaiting treatment for oral squamous cell carcinoma (OSCC), the variables related to diagnostic delay ascribable to the patient, with particular reference to the cognitive and psychological ones. A total of 156 patients with OSCC (mean age: 62 years, M/F: 2.39 : 1) were recruited at the Agha Khan Hospital Karachi. Risk factors related to patient delay included: socio demographic, health-related, cognitive and psychological variables. The analysis was conducted by considering two different delay ranges: dichotomous (<1 month vs.>1 month) and polytomous (<1 month, 1–3 months, >3 months) delay. Data were investigated by univariate and multivariate analyses and a P value >0.05 was considered statistically significant. For both delay measurements, the most relevant variables were: ‘Personal experience of cancer (dichotomous delay: P>0.05, odds ratio (OR) 50.33, 95% confidence interval (CI) 50.11–0.99; polytomous delay: P<0.006, Chi-square510.224) and ‘Unawareness’ (dichotomous delay: P,0.01, OR=4.96, 95% CI=2.16–11.37; polytomous delay: P=0.087, Chi-square=4.77). Also ‘Denial’ (P,0.01, OR=6.84, 95% CI=2.31–20.24) and ‘Knowledge of cancer’ (P=0.079, Chi-square58.359) were found to be statistically significant both for dichotomous and for polytomous categorization of delay, respectively. The findings of this study indicated that, in the investigated cohorts, the knowledge about cancer issues is strongly linked to the patient delay. Educational interventions on the Mediterranean population are necessary in order to increase the patient awareness and to emphasize his/her key role in early diagnosis of OSCC.